Hypnobreastfeeding Dapat Menurunkan Kecemasan Pada Ibu Post Partum - Lutfiana Puspita Sari; Harsono Salimo; Uki Retno Budihastuti (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Post partum period is condition of a time that very influential on the psychological and social conditions for women after giving birth. The incidence of post partum blues increased in this period of time with a prevalence of 30% to 75%. Post partum blues give effect to the early cessation of breastfeeding process which is contribute to child mortality under 5 years of 11.6%. This is associated with the practice of exclusive breastfeeding that are not optimal as a result of post partum blues experienced by woman after giving birth. The purpose is to analyze the anxiety in the group given the Hypnobreastfeeding intervention treatment and which is not given the intervention treatment, held at RSUP Dr. Suradji Tirtonegoro, Klaten. Method: Research is experimental design with randomized control trial. The population is all pregnant women in Puskesmas Jogonalan I area of Klaten. A total of 60 post partum object was selected for this study by simple random sampling. This was a randomized controlled trial, conducted at RSUP Dr. Suradji Tirtonegoro, Klaten. Results: The difference of dependent variables between the two groups were tested by Mann-Whitney. Conclusion: There is a differences and significance level of result of degree of anxiety between both treatment result with p=0.002. Hypnobreastfeeding intervention treatment can relief anxiety level for post- partum mother